Analysis of the Prescription of Antibiotics During the Implementation of COVID-19 Personal Protection Measures in a Regional Health System - Rojas-Garcia P; Antoñanzas F (Dove Medical Press, 2021)
Paula Rojas-Garcia, Fernando Antoñanzas Department of Economics and Business, University of La Rioja, Logroño, La Rioja, SpainCorrespondence: Paula Rojas-GarciaDepartment of Economics and Business, University of La Rioja, Logroño, La Rioja, SpainEmail paula.rojas@unirioja.esIntroduction: The rational consumption of antibiotics is a valuable goal for developed countries. Antibiotic resistance (AMR) was the main health threat before the coronavirus-19 (COVID-19) pandemic. To restrict COVID-19 transmission, the Spanish government implemented personal protection measures, including the decree of a lockdown. The objective of this study is to analyze the prescription of antibiotics during the implementation of COVID-19 personal protection measures in primary care in a Spanish region.Materials and Methods: Primary monthly official dispensations of antibacterials for systemic use (J01) were analyzed, disaggregating by clinical (active principle, age and sex of the patient) and socio-economic variables (basic health zone and level of income). Defined daily doses per thousand inhabitants (DID) prescribed in 2020 were compared with the prescription in 2019 using Chi-square test.Results: In 2020, the prescription of antibiotics (11.37 DID) was significantly lower (− 23.73%) than in 2019 (14.91 DID). The main reduction in the amount prescribed was found in May (− 42.64%). However, the prescription was significantly higher (71.34%) in February 2020 than in the same month in 2019 in nursing homes. In March 2020, prescriptions were lower (− 13.71%) than in the same month in 2019, except for the middle-income group, in which prescriptions were higher (9.67%), as well as azithromycin (10.11%). In April and May 2020, prescriptions were significantly lower than in 2019 in all age groups and both in women and men.Conclusion: Personal protection measures against COVID-19 transmission (lockdown, mask, social distance and increased hygiene) coincide in time with the greatest reduction in antibiotic prescription.Keywords: antibiotics, COVID-19, personal protection measures, co-payment